2012
DOI: 10.1111/j.1439-0531.2012.01996.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Dynamics, Interval to Ovulation and Fertility After AI in Short‐Term Progesterone and PGF2α Oestrous Synchronization Protocol in Sheep

Abstract: The study was aimed to assess the influence that short-term progesterone treatments have on follicular dynamics, oestrus and ovulation in sheep. The treatment was tested thereafter in a field trial to assess its fertility after AI with fresh semen. In a first experiment, 12 ewes without CL were grouped to receive a new (n = 6) or used CIDR (n = 6) for 7 days and blood samples were obtained to follow plasma progesterone profiles. In a second experiment, 39 cycling ewes were synchronized by a 7-day P4+PGF2α prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 30 publications
1
35
0
5
Order By: Relevance
“…It is interesting to note that the number of follicles ovulated averaged near 2.0 and that 30/33 (90.9%) of ovulatory-sized follicles at estrus, actually ovulated. In spite of having little relationship between antral follicular functionality and size (Cox et al, 2012), at least as observed in cattle (Geary et al, 2013), the 10% of large follicles that did not ovulate is a relatively small loss when compared to that observed in Suffolk and Texel ewes (>20%, Cox et al, unpublished). The breed was developed for twin lambing to minimize lambing attention (easy-care operation) and to optimize lamb survival, two of the most important economical traits in sheep production (Kleemann and Walker, 2005;Kleemann et al, 2006), therefore by the use of flushing this goal can be met.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…It is interesting to note that the number of follicles ovulated averaged near 2.0 and that 30/33 (90.9%) of ovulatory-sized follicles at estrus, actually ovulated. In spite of having little relationship between antral follicular functionality and size (Cox et al, 2012), at least as observed in cattle (Geary et al, 2013), the 10% of large follicles that did not ovulate is a relatively small loss when compared to that observed in Suffolk and Texel ewes (>20%, Cox et al, unpublished). The breed was developed for twin lambing to minimize lambing attention (easy-care operation) and to optimize lamb survival, two of the most important economical traits in sheep production (Kleemann and Walker, 2005;Kleemann et al, 2006), therefore by the use of flushing this goal can be met.…”
Section: Discussionmentioning
confidence: 74%
“…For instance, in small ruminants the administration of gonadotropins for superovulation may induce ovulation of large follicles at any moment after day 5 of the estral cycle (Cameron and Batt, 1991). In addition, estrous synchronization protocols may affect the number of ovulatory follicles, the interval to ovulation and the fertility of ewes depending on the steroidogenic status of larger follicles and may be a reason why eCG at low dosage is effective in controlling the interval to ovulation and fertility of ovulations, but not the number of ovulated follicles (Cox et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The estrus of the group was synchronized by a progesterone (CIDR G, InterAg, Hamilton, New Zealand) and PGF 2␣ (Cloprostenol, 0.5 mg i.m., Ciclase, Syntex, Argentine) protocol (Cox et al, 2012) combined with estradiol cypionate (ECP, 1 mg i.m., Pfizer, Sao Paulo, Brazil) 24 h after CIDR retrieval. Oestrous detection was confirmed by the tolerance exhibited by ewes to be mounted by a trained-vasectomized teaser that was handcontrolled by an experienced technician.…”
Section: Service Capacity Testmentioning
confidence: 99%
“…Conception rate was defined as the percentage of ewes pregnant after a synchronized estrous compared to those treated. Estrus was synchronized by a short-term treatment with a 6-day intravaginal progesterone (0.3 g progesterone, CIDR G, Pfizer) combined with prostaglandin F2␣ (0.125 mg, cloprostenol, Estrumate, Intervet, Friesoythe, Germany) at CIDR removal (Cox et al, 2012). Rams were introduced 24 h after CIDR removal for directed mating in a male to female ratio of 1:8-24.…”
Section: Reproductive Performancementioning
confidence: 99%